Gravitationally lensed quasars in Gaia – III. 22 new lensed quasars from Gaia data release 2. Issue 3 (10th December 2018) - Lemon, Cameron A; Auger, Matthew W; McMahon, Richard G
ABSTRACT: We report the discovery and spectroscopic confirmation of 22 new gravitationally lensed quasars found using Gaia data release 2. The selection was made using several techniques: multiple Gaia detections around objects in quasar candidate catalogues, modelling of unWISE coadd pixels using Gaia astrometry, and Gaia detections offset from photometric and spectroscopic galaxies. Spectra of 33 candidates were obtained with the William Herschel Telescope, 22 of which are lensed quasars, two highly probably lensed quasars, five nearly identical quasar pairs, one inconclusive system, and three contaminants. Of the three confirmed quadruply imaged systems, J2145+6345 is a 2.1 arcsec separation quad with four bright images ( G = 16.86, 17.26, 18.34, 18.56), making it ideal for time delay monitoring. Analysing this new sample alongside known lenses in the Pan-STARRS footprint, and comparing to expected numbers of lenses, we show that, as expected, we are biased towards systems with bright lensing galaxies and low source redshifts. We discuss possible techniques to remove this bias from future searches. A | b | > 20 complete sample of lensed quasars detected by Gaia and with image separations above 1 arcsec will provide a valuable statistical sample of around 350 systems. Currently only 96 known lenses satisfy these criteria, yet promisingly, our unWISE modelling technique is able to recover all of these with simple WISE- Gaia colour cuts that remove ∼80 per cent of previously followed-up contaminants. Finally, we provide an online data base of known lenses, quasar pairs, and contaminant systems.